Therapeutic Effect of Self-made Wrist Joint Flexion and Extension Orthoses Combined with Routine Rehabilitation Training on Wrist Joint Spasm after Brain Infarction - Rui JIAO; Shangjie CHEN; Shuqian LI; Xinyan JIA; Heng LIU (康复学报)
Objective:To observe the effect of self-made wrist joint flexion and extension orthoses combined with conventional rehabilitation treatment on wrist joint spasm in convalescent patients after cerebral infarction.Methods:A total of 60 patients with cerebral infarction were randomly assigned to wrist flexion-extension orthoses group and routine rehabilitation group according to the random number table method, with 30 cases in each group. Routine rehabilitation group was given convulsive electrical stimulation, electromyographic biofeedback, electronic biofeedback, job training, hand function training, exercise therapy, ordinary acupuncture and so on. The flexion and extension orthoses group was trained with flexion and extension device on the basis of routine rehabilitation treatment. The first treatment was carried out by the therapist for the patient, and then the patient was taught to operate. The flexion and extension device was fixed at one angle at each time. As the patient's joint activity gradually improved, the degree of the flexion and extension device was slowly raised before each treatment. The degree of adjustment per day was set up accoding to the patient's feeling of muscle tension without apparent pain. Convulsive electric stimulation was given for 15 minutes each time, and the rest routine rehabilitation was given for 20 minutes, once a day. The self-made wrist joint flexion and extension device was worn for 30 minutes each time, twice a day, six days a week for a total of three weeks. Before and after treatment, the upper limb motor function was assessed by simplified Fugl-Meyer motor function scale, the degree of carpal spasm was evaluated by modified Ashworth scale (MAS), and the modified Barthel index (MBI) was used to evaluate the degree of carpal spasm. MBI was used to evaluate the patient ability of daily living (ADL) and the sum of active flexion and extension of wrist joint was evaluated by goniometer, the hand function scale was assessed by the hand function scale.Results:After three weeks of treatment, the scores of Fugl-Meyer motor function scale in both groups were higher than those before treatment (P< 0.05), the increase of flexion and extension device group was more obvious than that of the routine rehabilitation group, the differences between the two groups were statistically significant after treatment (P< 0.05). After three weeks of treatment, the MAS scores of the two groups after treatment were lower than those before treatment (P< 0.05), and the decrease of the wrist flexion-extension orthoses group was more obvious than that of the routine rehabilitation group, the differences between the two groups were statistically significant after treatment (P< 0.05). After three weeks of treatment, the MBI scores of the two groups increased after treatment compared with that before treatment (P< 0.05), and the increase in the flexion and extension device group was more significant than that in the routine rehabilitation group, the differences between the two groups were statistically significant after treatment (P< 0.05); after three weeks of treatment, the sum of range of motion of the active flexion and extension activities of the wrist after treatment in both groups were increased compared with that before treatment (P< 0.05), and the increase in the flexion and extension device group was more significant than that in the conventional rehabilitation group, the differences between the two groups were statistically significant after treatment (P< 0.05); after three weeks of treatment, the hand function scale of the two groups increased after treatment compared with that before treatment (P< 0.05), and the increase in the wrist flexion-extension orthoses group was more significant than that in the routine rehabilitation group, the differences between the two groups were statistically significant after treatment (P< 0.05).Conclusion:Self-made wrist joint flexion and extension orthoses can reduce wrist spasm in convalescent patients after cerebral infarction, increase their active flexion and extension range of motion, improve their upper limb and hand function, and improve their daily life ability, without obvious side effects. It is worthy of clinical application promotion.